Sexual Segregation in Ungulates : Ecology, Behavior, and Conservation - Bowyer, R. Terry (Book collections on Project MUSE., 2022)
This book is essential reading for scientists, science students, and those interested in the conservation and management of species, including wildlife professionals, hunters, outdoor enthusiasts, and naturalists.